The construction of double type II heterostructure from CdS and Ni-MOF-74 with two structures and enhanced mechanism of photocatalytic water splitting - Niu, Lu; Zhang, Wang-gang; Li, Hao-tian; Wang, Hong-xia; Wang, Jian; Liu, Yi-ming (Journal of materials science, 2022)
Visible light-driven hydrogen production by water splitting has attracted much attention because of its advantages of low cost, relative safety, and environmental friendliness. In this paper, a series of Ni-MOF-74 materials, Ni-MOF-74(X), with different morphologies and structures were synthesized by controlling the amount (X mL) of added water. Then, various CdS/Ni-MOF-74 composites were prepared by simple mechanical mixing of Ni-MOF-74(X) and CdS nanoparticles. The morphology and structures of CdS, Ni-MOF-74(X), and CdS/Ni-MOF-74(X) were analyzed by SEM, TEM, XRD, FT-IR, BET, and XPS. The optical properties of the composites were analyzed by UV–visible DRS, PL, TRPL, and photoelectrochemical experiments. The results show that Ni-MOF-74 is formed with a Ni 3 (OH) 2 (H 2 O) 2 (tp) 2 structure (tp: terephthalate) at low water amounts and with a [Ni 3 (OH) 2 (H 2 O) 4 (tp) 2 ]·2H 2 O structure when sufficient water was present to promote its formation. Mixed structures of Ni-MOF-74 containing Ni 3 (OH) 2 (H 2 O) 2 (tp) 2 and [Ni 3 (OH) 2 (H 2 O) 4 (tp) 2 ]·2H 2 O are formed when the water amount is between 5 and 40 mL. The CdS/Ni-MOF-74(15) composite has the best photocatalytic hydrogen evolution performance under visible light irradiation, and the maximum produced hydrogen amount is 3117.9 μmol after 3 h, which is 12.8 times that of pure CdS nanoparticles. The composite of CdS and Ni-MOF-74 with a mixed structure exhibits better photocatalytic hydrogen production performance than the composite based on Ni-MOF-74 with a single structure. As an explanation for the superior activity, a double type II heterostructure is formed by CdS and Ni-MOF-74 with two structures. The photogenerated electrons in the conduction band (CB) of CdS spontaneously transfer to the CB of Ni-MOF-74, which is beneficial to the improvement in the separation of photogenerated carriers in hydrogen evolution.